2008
DOI: 10.1007/s00330-008-1112-9
|View full text |Cite
|
Sign up to set email alerts
|

“Tenomalacia”: a new sonographic sign of tendinopathy?

Abstract: The purpose of this study was to assess tendon compressibility with sonography in extensor tendinopathy and in asymptomatic extensor tendons of the elbow. Sonography of both elbows was performed in eight patients with a clinical diagnosis of unilateral lateral epicondylitis. Tendons were assessed for compressibility by measuring their thickness before and after compression with the transducer. The same manoeuvre was performed while tendon vascularity was assessed with colour Doppler. All eight cases showed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 8 publications
0
31
0
Order By: Relevance
“…These histopathologic alterations of tendinopathy have been found to increase the compressibility of tissue on ultrasound scans and may cause softening of the tissue on SE [33]. De Zordo et al reported that SE is valuable in the detection of intratendinous and peritendinous alterations in lateral epicondylitis or Achilles tendinopathy [23,34].…”
Section: Discussionmentioning
confidence: 99%
“…These histopathologic alterations of tendinopathy have been found to increase the compressibility of tissue on ultrasound scans and may cause softening of the tissue on SE [33]. De Zordo et al reported that SE is valuable in the detection of intratendinous and peritendinous alterations in lateral epicondylitis or Achilles tendinopathy [23,34].…”
Section: Discussionmentioning
confidence: 99%
“…Tendinosis involves collagen break down that softens and weakens the tendon, eventually leading to tendon tear or rupture [24]. These histopathologic alterations of tendinosis have been found to increase the compressibility of tissue at ultrasound, and may cause softening of tissue at SE [25]. De Zordo et al [26,27] reported that SE is valuable in the detection of the intratendinous and peritendinous alteration of lateral epicondylitis or Achilles tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Doppler on US might help us diagnose inflammation, degeneration, and to follow-up the evolution of such processes (4,14). This differentiation is very relevant, due to the fact that the goal of treatment and the prognosis changes substantially.…”
Section: Advantages Of Usmentioning
confidence: 99%